GIS modeling for selection of a transfer station site for residential solid waste separation and recycling - Pradhan, Biswajeet; Billa, Lawal (Universiti Putra Malaysia Press, 2013)
In this study a GIS model was developed and spatial analytical techniques performed to identify and select a suitable location for a waste transfer station in the sprawling suburban town of Petaling Jaya. The lack of a transfer station in urban centres of Malaysia has caused many problems and affects the efficiency of waste collection and disposal. With diminishing space for landfills and the increasing cost of solid waste management, the need for urban solid-waste recycling has become very important. However, finding a place for waste to be efficiently sorted before unwanted waste can be carried to disposal landfills has social and physical constraints. This study applies GIS techniques and analysis for site selection and identifies an acceptable area. In the model, environmental, physical and social constraints were taken into account, resulting in the selection of a potential area that is acceptable to the residents of the area because it is out of range of causing public nuisance and within minimum travelling distance for collection vehicles. The results show that the potential location for the transfer station should be in proximity of the industrial area of Petaling Jaya, allowing for the possible sale of recyclable materials to local industries. The location is also sited near a major highway to allow quick transportation of the rest of the unwanted waste to the landfill.